Cultural Breadth and Embeddedness: The Individual Adoption of Organizational Culture as a Determinant of Creativity. (June 2023) - Choi, Yoonjin; Ingram, Paul; Han, Sang Won
We propose that individuals differ in their ability to generate creative ideas as a function of the values, beliefs, and norms of their social group's culture they have adopted and routinely use. To generate creative ideas, an individual needs to think differently from their group to generate novel ideas that others cannot, while understanding what the group will view as appropriate and practical. We view culture as a network of cultural elements and decompose individuals' cultural adoption into two conceptually and empirically distinct dimensions. Cultural breadth, which reflects whether individuals have adopted a broad range of values, beliefs, and norms that span the organization's culture, contributes to the novelty required for creativity. Cultural embeddedness, which reflects whether individuals have adopted the core values, beliefs, and norms entrenched in the organization's culture, helps an individual generate ideas that others will view as useful. We predict that individuals with both high cultural breadth and high cultural embeddedness, who we label integrated cultural brokers, will be most likely to generate creative ideas that are novel and useful. We test and find support for our theory in two contexts: an e-commerce firm in South Korea and MBA students at a U.S. university.